In extremis diagnosis of celiac disease and concomitant wheat allergy - Borghini, Raffaele; Donato, Giuseppe; Marino, Mariacatia; Casale, Rossela; Di Tola, Marco; Picarelli, Antonio (Turkish Journal of Gastroenterology, 2018)
Abstract Celiac disease (CD) and concomitant wheat allergy are not commonly described in the literature. Both can have almost the same treatment consisting of a gluten-free or wheat-free diet. On the other hand, they are based on totally different pathogenetic mechanisms and can be easily underdiagnosed, particularly CD. We describe a peculiar case of a young female patient affected by wheat allergy whose serological and histological data were not diagnostic for CD. Organ culture system successfully detected specific antibodies for CD in duodenal biopsy supernatant, supporting the diagnosis of CD. Cite this article as: Borghini R, Donato G, Marino M, Casale R, Di Tola M, Picarelli A. In extremis diagnosis of celiac disease and concomitant wheat allergy. Turk J Gastroenterol 2018; 29: 515-7.